Decoding the western diet’s impact on cognition and blood biomarkers in Ossabaw pigs - Scott, Samantha (My University, 2025)
The use of swine has evolved far beyond their foundational agricultural purposes. Recent advancements in utilizing pigs as translational models for human medicine have significantly expanded our understanding of health and disease, not only in human medicine but also through an agrimedical lens. This thesis introduces a novel design of the 8-Arm Radial Maze to identify cognitive deficits and differences in blood biomarkers in Ossabaw pigs (CorVus Biomedical, Crawfordsville, IN; n = 32; boars and gilts), a well-established model of obesity, on either a healthy diet or a Western Diet. Additionally, this work advances previous research on physiological biomarkers by evaluating complete blood count and serum chemistry panels after 16 weeks. Study 1 aimed to assess cognitive impairment in Ossabaw pigs fed a normal diet or a Western Diet, which is a hypercaloric, high-fat, high fructose corn syrup formulated diet. A newly designed 8-Arm Radial Maze, capable of accommodating swine up to 200 kg, was used to assess key domains of cognition: working memory, reference memory, operant conditioning, and spatial discrimination learning. After 9 weeks of starting their respective diets, pigs began the first phase, conditioning, which included six sessions for acclimation and training. For conditioning, pigs were required to locate eight rewards, one in a bowl within each arm. In the second phase, acquisition, cognitive tasks required pigs to identify a unique configuration of only two correct bowls out of 8 across 15 sessions. Obese pigs exhibited early signs of cognitive impairment during the conditioning phase, such as reduced maze completion. These deficits were more distinct in the acquisition phase, with obese pigs entering fewer correct pods, taking longer to locate rewards, and spending more time in areas such as the arms, bowls, and center, which are behaviors indicative of distraction and reduced task efficiency. This study provides evidence that a pig model on the Western Diet can exhibit cognitive deficits as early as 9 weeks, potentially reflecting a potential nutrient and chronic inflammation effect on the brain. Study 2 aimed to improve understanding of peripheral biomarkers in the same pigs as Study 1 for 6 and 16 weeks on a Western Diet. Few studies included hematological findings in obese Ossabaw pigs, and experimental design and pig type varied. Blood samples were collected before starting the diet (baseline, covariate) and again at weeks 6 and 16 in relation to starting their respective diets. Sampling was performed using a Panepinto sling, a low-stress method that minimizes the stressor of handling and restraint, and isoflurane application. Notable hematological and physiological changes emerged at 6 and 16 weeks after starting their diets. Significant differences were observed in lipid metabolism, inflammatory markers, and blood cell profiles, suggesting early signs of immune dysregulation and metabolic dysfunction. Together, these studies conclude that the early stages of obesity are associated with both cognitive and hematological changes, highlighting a wide spectrum of physiological concerns linked to the Western Diet. In the face of a growing global obesity crisis and rising food insecurity, it is crucial to advance our understanding of obesity-related outcomes and emphasize the urgent need for early dietary intervention. Beyond biomedical relevance, these findings also carry important implications for the swine industry, where over-conditioning and metabolic disorders in breeding stock can impact productivity, longevity, and overall animal welfare. By bridging agrimedicine with applied animal science, this research underscores the value of using swine as a translational model that benefits both human health and livestock management practice.
Keywords: Obesity; Western diet; Pig; Swine; Neuroinflammation; Biomarkers